Assessment of The Melt Quality of a 30% Scrap ADC12 Aluminium Alloy using The Inclusion and Fluidity Measurement Instrument (IFMI) With Mullite Ceramic Filters - Ruri Lestari, Gusti Ruri; Riswan, Sandya Ananda; Anis, Muhammad; Ashari, Ahmad; Ayuningtyas, Paramita Vidya; Suharno, Bambang, Prof; Dhaneswara, Donanta (Journal of Materials Exploration and Findings, 2025)
The increasing demand for sustainable practices in the metal casting industry has driven the use of recycled aluminum alloys such as ADC12. However, the addition of aluminum scrap tends to increase oxide inclusions, which reduce melt fluidity and compromise casting quality. This study utilizes the Inclusion and Fluidity Measurement Instrument (IFMI), equipped with mullite ceramic filters, to assess the melt quality of ADC12 aluminum alloy containing 30% scrap. Fluidity and inclusion characteristics were evaluated at five pouring temperatures (660°C, 680°C, 700°C, 720°C, and 740°C). The results show that fluidity increased with temperature, reaching a peak of 84.6 g·s⁻¹ at 740°C, before declining due to excessive oxide inclusions. Quantitative analysis revealed that the average inclusion volume decreased from 0.257% in unfiltered samples to 0.114% in filtered ones, confirming the effectiveness of the filtration system. These findings demonstrate that IFMI can be used as a practical and real-time tool to evaluate melt quality in foundry applications, particularly when processing secondary aluminum alloys.